Preventing penetrating hand injuries in sabre fencing: an application and critique of the van Mechelen model by the Fédération Internationale d'Escrime - Harmer, P. A. (British Journal of Sports Medicine, 2015)
Background/aim: To address the unusual phenomenon of unbroken blades causing penetrating hand injuries in sabre fencing by applying the van Mechelen model of the `sequence of prevention`. Methods: Cases were collected from three surveillance systems and snowball sampling, and examined for potential aetiological factors. Presumed contributing factors were evaluated against the available evidence to compile a viable list for change. Determining a prevention strategy was guided by the philosophy of developing an approach that was most likely to produce a meaningful reduction in these injuries with the least disruption to the current norms of competitive sabre fencing. Results: Nine factors which contributed, either individually or in some combination, to these injuries were grouped under three headings relating to: (1) the nature of modern sabre fencing, (2) the design of the sabre blade and (3) the vulnerability of the hand. Changes to the design and integrity of sabre gloves were selected as the most feasible option and new standards were introduced as compulsory in international competitions from 1 April 2014. The effect of this change is now being monitored via available surveillance systems. Conclusions: The van Mechelen model is a useful framework for sports federations to apply to reduce injury risk, even for rare injuries. However, this research model has limitations in guiding the realities of sometimes competing interests among the scientific, political, financial and technical aspects of injury prevention interventions.